2016
DOI: 10.2196/humanfactors.5098
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Default Alarm Settings and Standard In-Service are Insufficient to Improve Alarm Fatigue in an Intensive Care Unit: A Pilot Project

Abstract: BackgroundClinical alarm systems safety is a national concern, specifically in intensive care units (ICUs) where alarm rates are known to be the highest. Interventional projects that examined the effect of changing default alarm settings on overall alarm rate and on clinicians’ attitudes and practices toward clinical alarms and alarm fatigue are scarce.ObjectiveTo examine if (1) a change in default alarm settings of the cardiac monitors and (2) in-service nursing education on cardiac monitor use in an ICU woul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(85 citation statements)
references
References 17 publications
2
81
0
2
Order By: Relevance
“…These alarms are known as "nuisance" alarms. The study by Sowan et al showed that most nurses interviewed strongly agreed that "nuisance" alarms are frequent, interrupt the care provided to patients, and reduce the reliability of alarms (11). When alarms are considered that way, professionals might disconnect and silence them, or ignore the warning that is intended to make a safer environment.…”
Section: Increase In Noise Caused By the Raise In The Number Of Alarmsmentioning
confidence: 99%
See 3 more Smart Citations
“…These alarms are known as "nuisance" alarms. The study by Sowan et al showed that most nurses interviewed strongly agreed that "nuisance" alarms are frequent, interrupt the care provided to patients, and reduce the reliability of alarms (11). When alarms are considered that way, professionals might disconnect and silence them, or ignore the warning that is intended to make a safer environment.…”
Section: Increase In Noise Caused By the Raise In The Number Of Alarmsmentioning
confidence: 99%
“…When alarms are considered that way, professionals might disconnect and silence them, or ignore the warning that is intended to make a safer environment. Instead of creating a safer environment, a high number of "nuisance" alarms assumes the opposite effect, resulting in desensitization (3,11) . This problem assumes special attention regarding low-priority alarms.…”
Section: Increase In Noise Caused By the Raise In The Number Of Alarmsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, although some system-based alarm management strategies achieved success in alarm reduction [14, 15], in other studies this success was not complemented with improvements in alarm fatigue or nurses’ attitudes toward alarm safety [9, 10]. Nurses reported the need for more training on physiologic monitors [9, 10]. It seems that the complexity of modern IT-equipped physiologic monitors requires structured individualized training focused on developing specific skill sets to navigate monitors and manage alarms [11, 12].…”
Section: Introductionmentioning
confidence: 99%